FAMILY DEVELOPMENT SESSION SEBAGAI UPAYA PEMBERDAYAAN MASYARAKAT DAN PENANGANAN KEMISKINAN (STUDI KASUS KEBIJAKAN SOSIAL PROGRAM KELUARGA HARAPAN DI KELURAHAN GIWANGAN KOTA YOGYAKARTA) - Dimas Purbo Pambudi; Titi Rahmawati; Chanifia Izza Millata; Titis Perdani; Neneng Sobibatu Rohmah; Muhammad Riyan Fitria Ramdlani (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2025)
Social Policy Program Keluarga Harapan (PKH) is a conditional cash transfer program from the Indonesian Ministry of Social Affairs. PKH is a family protection and social security-based policy that is often misunderstood as simply providing monetary social assistance. Therefore, the urgency of this research is important to discuss more deeply the most important benefits of PKH social policy implementation in Giwangan Village, Yogyakarta City. The purpose of this research is to describe and explore more deeply the existence of efforts to empower families by increasing knowledge to accelerate behavior change, this is through obtained from the family development session (FDS). At FDS there is a process of knowledge transfer from PKH Facilitators to PKH KPM which is carried out in group meetings, and the material comes from various material modules such as knowledge about managing the economy, being aware of health, education and childcare, and so on. The method in this research is descriptive qualitative, with data collection techniques of observation and in-depth interviews. The results of this study show that community empowerment through the implementation of FDS is to increase knowledge and cognitive abilities that have a positive impact on the formation of self-awareness, and accelerate behavior change for the better. The conclusion in this research shows that community empowerment in PKH and FDS activities can be practiced in everyday life as a provision to achieve a prosperous and poverty-free family.